2015
DOI: 10.1111/mmi.12936
|View full text |Cite
|
Sign up to set email alerts
|

Histidine phosphocarrier protein regulates pyruvate kinase A activity in response to glucose in Vibrio vulnificus

Abstract: The bacterial phosphoenolpyruvate:sugar phosphotransferase system (PTS) consists of two general energy-coupling proteins [enzyme I and histidine phosphocarrier protein (HPr)] and several sugar-specific enzyme IIs. Although, in addition to the phosphorylation-coupled transport of sugars, various regulatory roles of PTS components have been identified in Escherichia coli, much less is known about the PTS in the opportunistic human pathogen Vibrio vulnificus. In this study, we have identified pyruvate kinase A (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…We confirmed the latter association by steady-state kinetics (Supplementary Fig. 7a), and found that PykF is activated upon binding to non-phosphorylated HPr, suggesting that, similar to PykA 34 of V. vulnificus , HPr regulates PykF by increasing its affinity for phosphoenolpyruvate.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…We confirmed the latter association by steady-state kinetics (Supplementary Fig. 7a), and found that PykF is activated upon binding to non-phosphorylated HPr, suggesting that, similar to PykA 34 of V. vulnificus , HPr regulates PykF by increasing its affinity for phosphoenolpyruvate.…”
Section: Resultssupporting
confidence: 69%
“…Although not strictly membrane-bound 22 , HPr also co-purified with multiple regulatory targets (e.g., Adk, DhaK, PfkB, PykF; Supplementary Note 2). HPr is known to bind pyruvate kinase A (PykA) in the opportunistic pathogen Vibrio vulnificus 34 , whereas E. coli HPr interacts with an isozyme, pyruvate kinase 1 (PykF). We confirmed the latter association by steady-state kinetics (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The following supplements were added if necessary: kanamycin, 200 μg ml −1 for V. vulnificus and 50 μg ml −1 for E. coli ; ampicillin, 20 μg ml −1 for V. vulnificus and 100 μg ml −1 for E. coli ; chloramphenicol, 2 μg ml −1 for V. vulnificus and 10 μg ml −1 for E. coli ; isopropyl‐β‐D‐1‐thiogalactopyranoside (IPTG), 1 mM; L‐arabinose, 0.02%. Construction of the fapA deletion mutant was generated by allelic exchange using plasmid pDM4‐fapA (see Supporting Information experimental procedures and Table S2) as described previously (Kim et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Kim et al (15) showed that one of the three pyruvate kinases in Vibrio vulnificus, PykA, is activated by the non-phosphorylated form of HPr. The PTS, which catalyzes the first step of glycolysis, thus, also stimulates the final step in the presence of exogenous glucose through the direct interaction of HPr with the C-terminal domain of Vibrio PykA.…”
Section: Cro Articlementioning
confidence: 99%
“…The kinetics measured in the presence of HPr depend on its state of phosphorylation; PykF, PfkB, and NagB are activated by HPr but not HPr-P, whereas Adk is inhibited by HPr-P but not HPr. HPr is expected to be in the non-phosphorylated form when a PTS sugar such as glucose, N-acetylglucosamine, or fructose is present in the extracellular medium, and in the phosphorylated form in the absence of a PTS sugar (15,26). Thus, the phosphorylation state of HPr can be considered as an indicator of exogenous carbon and energy availability.…”
Section: Cro Articlementioning
confidence: 99%